INNOVATION OF INTEGRATIVE-INTERCONNECTIVE ISLAMIC EDUCATION BASED ON DIRECT EXPERIENCE IN UNIVERSITAS BRAWIJAYA MALANG - Chanifah, Nur (International Journal of Educational Management and Innovation, 2020)
Currently, the implementation of religious education is faced with various problems both internally such as its learning methodology, and externals such as the strengthening of the culture of materialism, consumerism, and hedonism, which has led to changes in people's lifestyle. In this context, it is very important for Islamic education innovations to improve the quality of Islamic education learning, to answer the challenges of globalization today. This study aims to find Islamic education learning innovations that are integrative-interconnective based on direct experience in Brawijaya University. Therefore, this research included case study research with data collection techniques using interviews, observation, and documentation. Data analysis uses descriptive-qualitative analysis. The results of the study show that Islamic education innovation in Brawijaya University covers several things, namely the paradigm, approach, strategy, method, and learning evaluation system. The learning paradigm is changed from dichotomous to integrative-interconnective, the learning approach is oriented towards student-centered with focus, namely problem, spiritual-scientific, and philosophical-normative. Learning strategies cover direct instruction, contextual teaching and learning, problem-based learning, and meaningful learning. Learning methods are oriented to direct experience. While the evaluation does not only lead to cognitive aspects but affective and psychomotor aspects by using observation and self-assessment techniques. The implications for understanding students are getting better. It can be seen in the result of student grades.